METHODOLOGY FOR TEACHING ENGLISH BASED ON INTERNET RESOURCES - Kenjabaev, Jahongir (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article considers the relevance of modern Internet technologies in the teaching of English, as well as analyzes the importance and effectiveness of using web technologies in the study of English, both in pairs and in the independent work of students.